CORPORATE INVESTMENT EFFICIENCY: THE ROLE OF ESG DISCLOSURE, FINANCIAL REPORTING QUALITY, AND DEBT MATURITY - Anisa; Stevanny (Universitas Serang Raya, 2026)
This study aims to analyze the effects of Environmental, Social, and Governance (ESG) disclosure, financial reporting quality, and debt maturity on the efficiency of investment in non-financial companies traded on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Using a quantitative approach with purposive sampling, the study analyzed 63 companies with a total of 315 annual observations. Data were collected from the official IDX portal, the Investment Gallery of Universitas Pamulang (UNPAM), and the companies’ official websites. Panel data regression methods using Eviews 12 were utilized to assess both the separate and collective influences of the variables. The results indicate that ESG disclosure and financial reporting quality don’t have a significant partial effect on investment efficiency. In contrast, debt maturity has a significant individual effect. However, when tested simultaneously, ESG disclosure, financial reporting quality, and debt maturity collectively have a significant impact on investment efficiency.